Construction and application of time-effect assessment database for experiments on war-traumatized animals. Issue 4 (11th November 2022) - Wang, Junkang; Wang, Jing; Zhang, Hongliang; Guo, Chengyu; Wang, Yanbiao; Lu, Bing; Feng, Cong; Pan, Fei; Li, Tanshi
Abstract: Background: High-quality real war trauma data are important, but they are still lacking. Using the database to realize the networked, systematic, standardized, and dynamic management of war injury animal experimental data can provide a real and reliable supplement for the research of war injury treatment. Methods: Through demand analysis, module design, architecture design, compilation and debugging, and other processes, JAVA language development tools were used to develop a time-effect assessment database for experiments on war-traumatized animals, where the browser/server architecture (B/S architecture) is used as the technical architecture and SQL Server as the database management system. Results: A time-effect assessment database for experiments on war-traumatized animals that features reasonable structural design, rich data resources, and convenient use has been established, in which case efficient collection, storage, display, retrieval, and management of animal experimental data have been achieved. At present, the database is running well and has good data quality.